The Influence of Country of Origin, Perceived Quality and Brand Image on Realme Smartphone Brand Purchase Intention - Sukmawati, Rifdah Ayu (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
This research is a quantitative explanatory study. This study aims to determine the effect of Country of Origin, Perceived Quality, and Brand Image on Purchase Intention of Realme Smartphone Brand on prospective smartphone buyers in Malang City. This study uses primary data whose data collection uses questionnaires and documentation. The analysis in this study uses quantitative analysis, multiple linear regression analysis and coefficient of determination analysis with the help of SPSS 25. The sample in this study were prospective smartphone buyers in Malang City totaling 130 people. The results of the study obtained using the t-test indicate that country of origin has a positive and significant effect on purchase intention, perceived quality has a positive and significant effect on purchase intention, and brand image has a positive and significant effect on purchase intention. In the coefficient of determination test, the data results obtained were 54.8% influenced by country of origin, perceived quality, and brand image, while the remaining 45.2% can be explained by the influence of other variables not studied.